Développement urbain durable et risques liés à l’eau : les pratiques du Nord au sein d’un territoire français en Amérique du Sud (Guyane française) - Richard Laganier; Franck Chow-Toun; Yannick Prats; Ambre Marsili (Territoire en Mouvement)
The integration of the principles of the sustainable development in the risk management related to water in urban environment questions the manner of conceiving the various forms of social, economic and environmental vulnerabilities and their interactions. The studied empirical case, the towns of French Guyana, also results in questioning the way in which a public action fits in the territory thought by a country of North (the Metropolitan France) whereas the dynamics are those of country of the South taking into account challenges to take up (strong demographic growth, poverty, pollution and flood in urban environment). That brings us to reflect on the installation of them principles of the sustainable development and the various public actions, to the city scale or others, in order to answer the space-time interdependences of the various stakes and themes which constitute the city.